Manifestation of The Pancasila Student Profile Strengthening Project as A Meaningful Learning : A Case Study - Pangestu, Iqbal Barkah; Wilodati, Wilodati; Hufad, Achmad (Universitas Pendidikan Mandalika, 2024)
This study examines the implementation of the Pancasila Student Profile Strengthening Project at SMAN 4 Bandung as a form of meaningful learning. This research used a qualitative approach with a case study method. Data were obtained through observations, interviews, and document analysis related to the project's implementation. Analysis of data using triangulation technique to reconfirm every data from a different view. The results showed that the Pancasila Student Profile Strengthening Project was designed to develop students' character and competence in accordance with Pancasila values. Students learn through direct experience and contextual cross-disciplinary projects relevant to their daily lives. Research orientation, case study, planning design, and implementation action designed in an exploratory and collaborative manner encourage students to hone their critical thinking skills, collaboration, and independence.